Molecular markers in breeding of ion-resistant barley varieties (review) - N. V. Novoselova; A. V. Bakulina (Аграрная наука Евро-Северо-Востока)
The review presents the perspectives of using DNA-markers in barley breeding for resistance to toxicity of aluminum, boron, manganese and cadmium ions. Currently, there have been identified quite a number of ion-resistance genes and quantitative trait loci (QTLs). Markers 1 kb-insertion and HvMATE-21indel that are linked to the HvAACT1 gene are recognized as standard gene-specific markers of aluminum resistance. Loci QTLs still require validation, but in the future they can serve as a basis for pyramiding several loci of aluminum tolerance in a single genotype. Molecular markers specific to the boron resistance genes of barley (HvBot1, HvNIP2;1 and HvBot2), and the QTL of barley resistance to the manganese toxicity (QSur.yf.3H) have also been developed. QTLs, genes, and markers related to low cadmium accumulation were identified in barley. Most studies focus on finding and developing markers linked to ion resistance rather than on their practical application in plant selection. However, breeding programs have already used markers related to the resistance of barley to high concentrations of aluminium and boron ions. Marker-assisted selection has high potential, and in course of time advances in science make its technologies more accessible, easier, and less expensive.